PERUMUSAN STRATEGI PEMASARAN PRODUK MINUMAN BOBA “MIXUE” DENGAN MENGGUNAKAN MATRIKS INTERNAL EKSTERNAL - Ni Luh Gede Sari Marta Kyana; A. A. Ayu Tirtamara; Ni Nyoman Kerti Yasa (PT Naureen Digital Education, 2023)
The purpose of this research is to find out an attractive marketing strategy for Mixue Boba Drink in facing very tight competition. The approach used in this research is the SWOT Analysis and Internal-External Matrix. SWOT analysis is used to identify external factors (opportunities and threats) and internal factors (strengths and weaknesses). The results of the study based on internal external matrix analysis, it can be identified that the Raya Dalung